DIVERSIDAD MALACOLÓGICA EN LA REGIÓN MAYA. II. “PARQUE ESTATAL AGUA BLANCA”, TABASCO, MÉXICO - Rangel Ruíz, Luis José; Gamboa Aguilar, Jaquelina; Alegría Ruiz, Froylan (Instituto de Ecología, A.C., 2004)
In 1996 and 1998, a collection of gasteropods was made in the Agua Blanca State Park in order to establish their taxonomic identity and geographic distribution. From this collection, 23 species (1 freshwater and 22 terrestrial) were found to be Prosobranchia (26.1%) and Pulmonata (73.9%). For the Prosobranchia specie, half of them were observed to be Mesogastropoda and the other half Archaeogastropoda; while the Pulmonata specie was encountered to have 100 % of Stylommatophora. The specie´s richness was 23. The geographic distribution of the species, restricted to the Mesoamerican Neotropical region, was the main zoographic component with 78.3% (43.5% Mesoamerican Neotropical species with the addition of 34.8 % Mexican Neotropical endemics). The endemic species of Mexico represented 40%, from which 8 % were endemic to Tabasco.